Effectiveness Of Combination Of Meditation And Positive Affirmations On Labor Duration And Apgar Score - Evi Zahara; Iin Fitraniar; Rahmi Rahmi; Emilda AS (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Meditation and positive affirmations are part of non-pharmacological therapies to treat anxiety in pregnant women. Anxiety generally occurs in third trimester pregnant women. Anxiety can increase catecholamines which have a negative impact on the mother and fetus both during pregnancy and childbirth.Purpose: This study was to analyzed the combined effect of meditation and positive affirmations on labor duration and APGAR scoresMethod: iThis istudy iuses a quasi experimental design with a post test only control group approach. The research subjects were third trimester primigravida, totaling 24 people who were divided into 2 groups. Data were analyzed using the Independent sample t-test.Results: There was a significant difference in the length of labor with p-value = 0.017 (p<0.05) and APGAR scores with p-value = 0.020 (p<0.05) compared between the control group and the treatment group.Conclusion: the combination of meditation and positive affirmations is effective in shortening the length of labor and increasing the APGAR scores.Suggestion: midwifery service providers can apply a combination of meditation and positive affirmations for third trimester pregnant women in order to minimize problems that affect the length of labor and the APGAR scores of newborns. Kata Kunci : APGAR Score, Duration of labor, Combination Meditation and Positive Affirmations.